Tryptophan in the mouse diet is essential for embryo implantation and decidualization - Chen, Si-Ting; Ran, Feng; Shi, Wen-Wen; Liu, Cheng-Kan; Wang, Peng-Chao; Luo, Hui-Na; Yang, Zeng-Ming (Frontiers in Endocrinology, 2024)
Nutritional deficiency occurs frequently during pregnancy and breastfeeding. Tryptophan (Trp), an essential amino acid which is critical for protein synthesis, serves as the precursor for serotonin, melatonin, and kynurenine (Kyn). The imbalance between serotonin and kynurenine pathways in Trp metabolism is closely related to inflammation and depression. This study assessed the effects of Trp deficiency on mouse early pregnancy. Embryo implantation and decidualization were analysed after female mice had been fed diets containing 0.2% Trp (for the control group), 0.062% Trp (for the low Trp group) and 0% Trp (for the Trp-free group) for two months. The uteri of the mice were collected on days 4, 5, and 8 of pregnancy. On day 8 of pregnancy, the number of implantation sites were found to be similar between the control and the low Trp groups. However, no implantation sites were detected in the Trp-free group. On day 5 of pregnancy, plane polarity- and decidualization-related molecules showed abnormal expression pattern in the Trp-free group. On day 4 of pregnancy, there was no significant difference in uterine receptivity molecules between the low-Trp group and the control group, but uterine receptivity was abnormal in the Trp-free group. At implantation sites of the Trp-free group, IDO and AHR levels were markedly elevated. This potentially increased levels of Kyn, 2-hydroxy estradiol, and 4-hydroxy estradiol to affect decidualization. Hence, Trp-free diet may impair decidualization via the IDO-KYN-AHR pathway.